Regulating effects of triptriolide on the proliferation and apoptosis of splenic lymphocyte in vivo and in vitro - Yiqi YANG; Xiaowan WANG; Wanlin YU; Lihua HUANG; Yunshan WU; Xiaodong HAN; Fangfang XU; Wei MAO; Peng XU; Bo LIU (KeAi Communications Co., Ltd., 2022)
Objective: Triptriolide (T11) is isolated from the Chinese herb Tripterygium wilfordii Hook F (TwHF), which has been used as an immunosuppressive reagent for many years in China, while the role of this compound in TwHF is still unknown. In this study, we try to investigate the immune regulating effects of T11 on the proliferation and apoptosis of splenic lymphocyte in vivo and in vitro. Methods: we pretreated the BALB/c mice with T11 (2.8, 14, 28 mg/kg) and prednisone acetate (PA, 1.3 mg/kg, positive control) for 7 days before lipopolysaccharides (LPS, 3 mg/kg) stimulation. Then the histopathologic change of spleen was examined by H&E method, and the apoptosis of splenic lymphocyte was assessed by flow cytometry method. In addition, we further studied the inhibition effect of T11 (50, 100, 150, 200 µg/mL) on the proliferation and activity of splenic lymphocyte, which was with or without the stimulation of concanavalin A (Con A, 5 µg/mL) and lipopolysaccharides (LPS, 5 µg/mL) in vitro, respectively. Results: We found that T11 not only can restore the pathogenesis process in spleen, and boost the splenic lymphocyte apoptosis in vivo, but also can inhibit the splenic lymphocyte proliferation and affect its viability in vitro. Conclusion: The results indicated that T11 might modulate the immune function of LPS-induced BALB/c mice by inhibiting the proliferation and inducing the apoptosis of splenic lymphocyte. Therefore, T11 could be a novel immunomodulator in autoimmune disease treatment in clinical.